Implementasi Kewirausahaan Sosial pada Layanan Penjemputan dan Pengelolaan Barang Bekas Ruang Tilas - Dindasari, Rima Nur; Supiyadi, Dedi (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This study analyzes the implementation of social entrepreneurship in Ruang Tilas' used goods pick-up and management service using qualitative and descriptive methods, with data from interviews and academic sources. SWOT and TOWS analysis show that Ruang Tilas has strengths in business innovation, brand awareness, strong partnerships, and opportunities from increasing environmental awareness and government support, but faces challenges of limited resources, technology, competition, and regulatory changes. The right strategy allows Ruang Tilas to leverage strengths and opportunities to overcome weaknesses and threats, such as expanding services, running educational campaigns, obtaining government funding support, seeking strategic partnerships, and investing in technology. The Business Model Canvas shows Ruang Tilas' focus on environmentally friendly services with revenue from picking up and selling recycled goods, supported by fleets, staff, and strategic partnerships so that it can provide a sustainable positive impact on the environment and society.